Analysis performance of L-PPM infrared wireless communications for indoor LOS and diffuse links - Sahthong, J.; Wonghoori, S.; Noppanakeepong, S.; Manyanon, A. (My University, 2003)
In this paper, we present the efficiency and performance of Pulse Position Modulation (L-PPM) for indoor wireless infrared communication system. By physical characteristic of mfrared channels using intensity modulation with direct detection (IMIDD). Noise in the channel will be considered as Additive - White Gaussian Noise. We evaluate power and bandwidth efficiency compared with On Off Keying (OOK). We have computed the path loss versus horizontal separation between transmitter and receiver in LOS and Diffise link, and our results show the best average . power efficiency among the modulation techniques, which art presented for 2, 4, 8, 16, 32, and 64 PPM at bit rates of 10 Mb/s to 100 Mb/s. Finally, we present Monte Carlo Simulation results to Bit Error Probability and the best Signal to Noise Ratio that LPulse Position Modulation requirement.
Keywords: Diffuse link; IM/DD; L-PPM; LOS